Auto Tech Enterprise semi auto trash can compactor / Nur Aina Maizan Kamaruddin - Kamaruddin, Nur Aina Maizan (2020)
The main product is a trash can compactor. We produce a semi automatic trash can compactor based on current technology. The company plans to offer a high quality of trash can compactor at a competitive price. Auto Tech Enterprise has produced a number of innovative trash can compactor designs to distinguish its quality as the only one of its kind and is especially remarkable and exceptional compared to other competitors. To make this even more appealing and interesting, the company wants to make some differences by imagination creation. The trash can compactor is specifically designed to ease the customers to manage their garbage or waste materials at home or office. The uniqueness of this product and the quality of the raw material we use to produce this product will surely attract the consumer to buy it. This trash can compactor has its own benefits and it can reduce many problems especially in the waste management process.